Avaliação toxicológica de compostos orgânicos de telúrio sobre o desenvolvimento pré-natal em camundongos - Roman, Silvane Souza (2011)
It is known that most chemical agents readily cross the placenta and thus may be considered that maternal exposure to external agents can result in toxic effects on embryo-fetal organism. Considering the chemical characteristics of organotellurium compounds, such as lipid solubility and molecular weight that facilitate the cross placental barrier, toxicological studies should be conducted to verify the effects of these compounds on intrauterine development in experimental models. Furthermore, organotellurium compounds have been reported as a promising alternative in health by showing pharmacological properties in different models in which oxidative stress plays a role. Based on these considerations, this thesis investigated the toxic effects of organotellurium compounds, with emphasis on embryonic and fetal development in mice. Article 1, the maternal exposure to diphenyl ditelluride (PhTe)2 at single dose of 60 mg/kg, s.c on GD 4 or GD 14 was embryotoxic in the absence of maternal toxicity but different from the results in rats, which was toxic to the dams and teratogenic to fetus at dose extremely lower than that of mice. These findings showed that pharmacokinetic factors may be involved in susceptibility to teratogenesis differences between rats and mice as well as the period of gestation. In the first manuscript, mice orally exposed to a single dose of 32.8 mg/kg of 1-butyltellurenyl-2-methyl thioheptene (BTMT) at GD 8, one day of the organogenesis period, did not altered the parameters of maternal and fetal oxidative stress, but was embryolethal in the absence of maternal toxicity. These results indicate embryolethality caused by BTMT in mice. In the second manuscript, the exposure to 2-phenylethynyl-butyl tellurium (PEB) in mice at single dose of 10 mg/kg did not induce maternal toxicity, but affect the reproductive sucess at GD 14. In mice, the acute exposure to different organotellurium compounds at doses considerably high showed adverse effects on intrauterine development ranging from discrete embryotoxic insult to embryolethality. We assume that the main reason for the different effects found for PEB and BTMT when compared to (PhTe)2 is that the molecular structures of these organotellurium are very different. Ditellurides are more reactive than tellurides because of the weak Te-Te bond when compared to the Te-carbon bond, since biotransformation process has been seem to be important for the actions of these compounds in vivo. Together, these data suggest that acute exposure to different organic compounds of tellurium induced adverse effects on intrauterine development dependent on the route of administration, the chemical structure of compounds, dose, animal species and period of gestation, therefore making it difficult to compare effects seen in the article with the results of manuscripts 1 and 2, but that does not impossible or discarded the importance of continuity and further research into the pharmacological and toxicological properties of these compounds.